2011
DOI: 10.1093/nar/gkq1342
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic profile of the euchromatic region of human Y chromosome

Abstract: The genome of a multi-cellular organism acquires various functional capabilities in different cell types by means of distinct chromatin modifications and packaging states. Acquired during early development, the cell type-specific epigenotype is maintained by cellular memory mechanisms that involve epigenetic modifications. Here we present the epigenetic status of the euchromatic region of the human Y chromosome that has mostly been ignored in earlier whole genome epigenetic mapping studies. Using ChIP-on-chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…To illustrate, in order to understand how chromatin reorganizes during gonadogenesis, Maatouk et al () performed genome‐wide DNaseI hypersensitivity mapping (DNaseI‐seq), an assay that allows locating and characterizing regulatory regions of the genome based on the property that they are depleted of nucleosomes. Another interesting approach is the study of Singh et al (). Using a ChIP‐on‐chip approach, they mapped different histone modifications, including H3K9ac, H3K9me3, and H3K27me3, and CTCF (a.k.a.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, in order to understand how chromatin reorganizes during gonadogenesis, Maatouk et al () performed genome‐wide DNaseI hypersensitivity mapping (DNaseI‐seq), an assay that allows locating and characterizing regulatory regions of the genome based on the property that they are depleted of nucleosomes. Another interesting approach is the study of Singh et al (). Using a ChIP‐on‐chip approach, they mapped different histone modifications, including H3K9ac, H3K9me3, and H3K27me3, and CTCF (a.k.a.…”
Section: Perspectivesmentioning
confidence: 99%
“…Another interesting approach is the study of Singh et al (2011). Using a ChIP-on-chip approach, they mapped different histone modifications, including H3K9ac, H3K9me3, and H3K27me3, and CTCF (a.k.a.…”
Section: Perspectivesmentioning
confidence: 99%
“…While some autosomal or X‐linked genes seem to be involved in various spermatogenic stages (Dohle et al ., ; Kukuvitis et al ., ), there is an increasing evidence that several important genes are located on the long arm of the Y chromosome, and particularly in the azoospermia factor (AZF) regions AZFa, AZFb and AZFc (Navarro‐Costa et al ., ; Massart et al ., ). Located in these regions, there are some gene families referred as the DAZ , TSPY , RBMY and TTTY genes (Arnemann et al ., ; Ma et al ., ; Krausz & Fellous, ; Skaletsky et al ., ; Singh et al ., ). Deletions in the AZF region have been suspected to be one of the main genetic causes of male infertility (Tiepolo & Zuffardi, ; Schnieders et al ., ; Vogt et al ., ; Pryor et al ., ; Ferlin et al ., ; Simoni et al ., ; Krausz et al ., ; Hsu et al ., ; EAU, ; Singh et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Singh et al (23) demonstrated by large-scale epigenomic analysis the transcriptional potential of all protein-coding genes on the Y-chromosome including the SRY and the oncogene TSPY . According to the authors, the GBY locus may be hypomethylated in gonadoblastomas, resulting in overexpression of the TSPY and TTTY genes (24,25).…”
Section: Introductionmentioning
confidence: 99%